TRACKING EFFECT ELECTRONIC DATA OPERATING SYSTEMS IN AUDITING TECHNOLOGY AND THE QUALITY OF THE EXTERNAL AUDITOR’S PERFORMANCE (World Economics and Finance Bulletin, 2024)
The complexity of electronic data operation systems in light of the progress of information technology in the business environment is the cause of the development of the auditing profession and has significantly affected the use of auditing technology to enhance the quality of external auditor performance. The research aims to analyze the impact of the complexity of electronic data operation systems on the quality of external auditor performance and understand how the complexity of systems affects the auditor's ability to conduct an effective and comprehensive audit. The deductive approach was adopted in the theoretical aspect, and in the practical aspect, the questionnaire was analyzed and distributed to the research sample using SPSS statistical programs to show the correlation and influence between the research variables. The research results indicate that the use of audit technology according to the environment of the complexity of electronic operating systems leads to raising the efficiency of the external auditor. The most important recommendations were the need to adopt the use of audit tools based on information technology in analyzing big data, to improve the ability of auditors to detect violations and analyze data more accurately
Keywords: Information Systems; Audit Technology; Quality Of External Auditor’s Performance